Chitin-Glucan Complex Hydrogels: Optimization of Gel Formation and Demonstration of Drug Loading and Release Ability - Araújo, Diana (2022)
Chitin-glucan complex (CGC) hydrogels were fabricated through a freeze–thaw procedure for biopolymer dissolution in NaOH 5 mol/L, followed by a dialysis step to promote gelation. Compared to a previously reported methodology that included four freeze–thaw cycles, reducing the number of cycles to one had no significant impact on the hydrogels’ formation, as well as reducing the total freezing time from 48 to 18 h. The optimized CGC hydrogels exhibited a high and nearly spontaneous swelling ratio (2528 +- 68%) and a water retention capacity of 55 +- 3%, after 2 h incubation in water, at 37 ºC. Upon loading with caffeine as a model drug, an enhancement of the mechanical and rheological properties of the hydrogels was achieved. In particular, the compressive modulus was improved from 23.0 +-0.89 to 120.0 +- 61.64 kPa and the storage modulus increased from 149.9 +- 9.8 to 315.0 +- 76.7 kPa. Although the release profile of caffeine was similar in PBS and NaCl 0.9% solutions, the release rate was influenced by the solutions’ pH and ionic strength, being faster in the NaCl solution. These results highlight the potential of CGC based hydrogels as promising structures to be used as drug delivery devices in biomedical applications